Sphingosine-1-phosphate receptor-independent lung endothelial cell barrier disruption induced by FTY720 regioisomers. (February 2020) - Camp, Sara M.; Marciniak, Alexander; Chiang, Eddie T.; Garcia, Alexander N.; Bittman, Robert; Polt, Robin; Perez, Ruth G.; Dudek, Steven M.; Garcia, Joe G. N.
Rationale: Vascular permeability is a hallmark of acute respiratory distress syndrome (ARDS) and ventilator-induced lung injury pathobiology; however, the mechanisms underlying this vascular dysregulation remain unclear, thereby impairing the development of desperately needed effective therapeutics. We have shown that sphingosine-1-phosphate (S1P) and 2-amino-2-(2-[4-octylphenyl]ethyl)-1, 3-propanediol (FTY720) analogues are useful tools for exploring vascular barrier regulation mechanisms. Objective: To experimentally define the effects of FTY720 regioisomers on lung endothelial cell barrier regulation. Methods: Specific barrier-regulatory receptor and kinase inhibitors were utilized to probe signaling mechanisms involved in FTY720 regioisomer-mediated human lung endothelial cell barrier responses (trans-endothelial electrical resistance, TER). Docking simulations with the S1P1 receptor were performed to further evaluate FTY720 regioisomer signaling. Results: FTY720 regioisomers produced potent endothelial cell barrier disruption reflected by declines in TER alterations. Pharmacologic inhibition of Gi-coupled S1P receptors (S1P1, S1P2, S1P3) failed to alter FTY720 regioisomer-mediated barrier disruption; findings that were corroborated by docking simulations demonstrating FTY720 regiosomers were repelled from S1P1 docking, in contrast to strong S1P1 binding elicited by S1P. Inhibition of either the barrier-disrupting PAR-1 receptor, the VEGF receptor, Rho-kinase, MAPK, NFkB, or PI3K failed to alter FTY720 regioisomer-induced endothelial cell barrier disruption. While FTY720 regioisomers significantly increased protein phosphatase 2 (PP2A) activity, PP2A inhibitors failed to alter FTY720 regioisomer-induced endothelial cell barrier disruption. Conclusions: Together, these results imply a vexing model of pulmonary vascular barrier dysregulation in response to FTY720-related compounds and highlight the need for further insights into mechanisms of vascular integrity required to promote the development of novel therapeutic tools to prevent or reverse the pulmonary vascular leak central to ARDS outcomes.